Penggunaan Media Sosial Tik-Tok terhadap Pengungkapan Diri (Self Disclosure) Remaja di Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas - Parapat, Rizka Wahyuni (Lembaga Yasin AlSys, 2023)
This study examines the use of Tik-Tok social media for adolescent self-disclosure in Sibuhuan, Barumun District, Padang Lawas District, which is focused on adolescent self-disclosure in Sibuhuan, Barumun District, Padang Lawas District. This research uses descriptive method with qualitative analysis. The informants of this study were teenagers around Barumun District, Padang Lawas Regency. The method used is the method of observation, interviews and documentation. The theory used in the discussion is the Johari Window Theory put forward by Joseph Luft and Harry Ingham. There were seven subjects in this study, namely Ningky Aminarti, Sadimah Pulungan, Hery Sahputra Harahap, Nur Sawalidah Piliang, Suryani Harahap, Jamaluddin and Raja Imam Pulungan. The results of this study indicate that there is self-disclosure by adolescents through tick-tock, namely expressively with open self as an enlarged area and implied self-disclosure with hidden self as an enlarged area. The functions of self-disclosure carried out by teenagers through tick-tock are expression functions, self-validation functions, self-clarification functions and social control functions.